Hermetic control treatment of P. truncatus (horn) (coleptera: bostrichidae) infestation on stored dried cassava chips in poly then bags (2011)
The focus of this research work was on the hermetic control treatment against Prostephanus truncatus Horn, 1878 infestation on dried cassava chips, over an infestation period of 10 weeks in the store. The experimental set-up was done in three hermetic treatments, this include, single bag, double bags and triple bags treatment. Each treatment was replicated 15 times. The used bags were made up of polythene material, with 0.056 mm thickness and 360 mm x 600 mm in dimension. The bags were made air tight by fasten the opening with twine. Each set - up contained 20 kg of dried cassava chips and 30 adults P.truncatus. These were stored in the laboratory. At the end of the storage period, P. truncatus rate of emergence and weight loss in dried cassava chips decreased with increase in the treatment bag layers. Furthermore, mortality rate in P. truncatus decreased with increased treatment bags layers. The use of polythen bag hermetic treatment technique converse protection on stored dried cassava chips. However, triple bags layers treatment was the most effective for P. truncatus control.